React and React Native : build cross-platform JavaScript applications with native power for the web, desktop, and mobile - Boduch, Adam; Derks, Roy; Sakhniuk, Mikhail (Packt Publishing Ltd., 2022)
Over the years, React and React Native has proven itself among JavaScript developers as a popular choice for a complete and practical guide to the React ecosystem. This fourth edition comes with the latest features, enhancements, and fixes to align with React 18, while also being compatible with React Native. It includes new chapters covering critical features and concepts in modern cross-platform app development with React. From the basics of React to popular components such as Hooks, GraphQL, and NativeBase, this definitive guide will help you become a professional React developer in a step-by-step manner. You'll begin by learning about the essential building blocks of React components. As you advance through the chapters, you'll work with higher-level functionalities in application development and then put your knowledge to work by developing user interface components for the web and native platforms. In the concluding chapters, you'll learn how to bring your application together with robust data architecture. By the end of this book, you'll be able to build React applications for the web and React Native applications for multiple mobile platforms.